Isohypsibius qinlingensis sp. nov. (Tardigrada, Hypsibiidae) from China - Li, Xiaochen; Wang, Lizhi; Yu, Di (Zootaxa, 2005)
Isohypsibius qinlingensis sp. nov. is described from China. Isohypsibius qinlingensis sp. nov. differs from all known Isohypsibius species with large gibbosities and two macroplacoids in the numbers and arrangement of gibbosities in each row. The new species is similar to Isohypsibius roncisvallei (Binda & Pilato, 1969), but it differs from it in having different arrangement of the gibbosities, and having densely arranged small tubercles on dorsal and lateral side of the body.